Labeling Same-Sex Sexuality in a Tolerant Society That Values Normality: The Dutch Case. Issue 13 (10th November 2018) - van Lisdonk, Jantine; Nencel, Lorraine; Keuzenkamp, Saskia
ABSTRACT: Studies have pointed to a trend in Western societies toward the normalization of homosexuality and emerging "post-gayness" among young people, who no longer consider their sexual identity meaningful in defining themselves. This article takes a closer look at the Dutch case where tolerance is regarded as a national virtue, while society remains heteronormative. In 38 interviews with Dutch same-sex-attracted young people, we investigated the labels they used to describe their sexual orientation to reveal what they can tell us about normalization, tolerance, and heteronormativity. In their labeling strategies, participants de-emphasized their sexual identity, othered, and reinforced the hetero/homo binary. They preferred labels without connotations to gender expression. While post-gay rhetoric was ideologically appealing, its use was not an outcome of their sexual orientation having become insignificant; it rather enabled them to produce normality. We discuss the findings against the backdrop of "Dutch tolerance, " which rests on an ideology of normality.